Eugenol Ester Derivatives: Synthesis, Insecticidal Activity and Computational Studies - José R. A. Coelho; Tatiana F. Vieira; Renato B. Pereira; David M. Pereira; Elisabete M. S. Castanheira; A. Gil Fortes; Sérgio F. Sousa; Maria José G. Fernandes; M. Sameiro T. Gonçalves (Chemistry Proceedings, 2021)
Specific structural modifications in eugenol molecules can simultaneously improve the biological activity and reduce side effects of the respective analogues. The esterification of eugenol by two different experimental procedures, and subsequently the conversion of one of the esters into the corresponding oxirane, was carried out. All derivatives obtained were then evaluated for their effect on the viability of Sf9 (Spodoptera frugiperda) cells. In addition, a structured-based inverted virtual screening protocol was employed to identify the potential proteins associated with the observed insecticidal activity. The encouraging results obtained allowed us to establish a preliminary structure–activity relationship.